Pharmacological Inhibition of NLRP3 Inflammasome Attenuates Myocardial Ischemia/Reperfusion Injury by Activation of RISK and Mitochondrial Pathways. (8th December 2016) - Mastrocola, Raffaella; Penna, Claudia; Tullio, Francesca; Femminò, Saveria; Nigro, Debora; Chiazza, Fausto; Serpe, Loredana; Collotta, Debora; Alloatti, Giuseppe; Cocco, Mattia; Bertinaria, Massimo; Pagliaro, Pasquale; et al.
Abstract : Although the nucleotide-binding oligomerization domain- (NOD-) like receptor pyrin domain containing 3 (NLRP3) inflammasome has been recently detected in the heart, its role in cardiac ischemia/reperfusion (IR) is still controversial. Here, we investigate whether a pharmacological modulation of NLRP3 inflammasome exerted protective effects in an ex vivo model of IR injury. Isolated hearts from male Wistar rats (5-6 months old) underwent ischemia (30 min) followed by reperfusion (20 or 60 min) with and without pretreatment with the recently synthetized NLRP3 inflammasome inhibitor INF4E (50  μ M, 20 min before ischemia). INF4E exerted protection against myocardial IR, shown by a significant reduction in infarct size and lactate dehydrogenase release and improvement in postischemic left ventricular pressure. The formation of the NLRP3 inflammasome complex was induced by myocardial IR and attenuated by INF4E in a time-dependent way. Interestingly, the hearts of the INF4E-pretreated animals displayed a marked improvement of the protective RISK pathway and this effect was associated increase in expression of markers of mitochondrial oxidative phosphorylation. Our results demonstrate for the first time that INF4E protected against the IR-induced myocardial injury and dysfunction, by a mechanism that involves inhibition of the NLRP3 inflammasome, resulting in the activation of the prosurvival RISK pathway and improvement in mitochondrial function.